1995
DOI: 10.1002/jbmr.5650100502
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spontaneous calcium intake and physical exercise on the vertebral and femoral bone mineral density of children and adolescents

Abstract: Peak bone mass is determined mainly by genetic-ethnic factors, but environmental factors such as calcium intake and physical activity during childhood and adolescence could play a role. We have measured the bone mineral density (BMD) of 151 healthy children and adolescents, ages 7-15.3 years. Density was measured by dual X-ray absorptiometry (DXA) at two sites (lumbar verterbrae L1-L4 and the upper femur), and the data were analyzed in terms of the height, weight, sexual maturation, spontaneous calcium intake,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(46 citation statements)
references
References 29 publications
7
31
0
8
Order By: Relevance
“…38 In a randomized controlled trial performed in identical twins, Johnston et al 11 found that daily administration of calcium 1000 mg to 1 member of the pair resulted in a significant gain in bone mass after 3 years. This positive impact disappeared during and after puberty.…”
Section: Resultsmentioning
confidence: 99%
“…38 In a randomized controlled trial performed in identical twins, Johnston et al 11 found that daily administration of calcium 1000 mg to 1 member of the pair resulted in a significant gain in bone mass after 3 years. This positive impact disappeared during and after puberty.…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of studies that have shown the effectiveness of calcium on bone mineralization (6,7); however, several studies did not demonstrate any such role (8,9). There may be several reasons for these confl icting results.…”
mentioning
confidence: 99%
“…Calcium intake has been shown to correlate with bone density in healthy children (23), and maintaining adequate calcium intake during childhood and adolescence is necessary to attain a normal peak bone mass, which may be important in reducing the risk of fractures and osteoporosis later in life (24).…”
Section: Discussionmentioning
confidence: 99%